Uma análise da obra “Paideia” de Werner Wilhelm Jaeger: educação, cultura, ética e política na Antiguidade grega. - Soares, Heverton (2022)
The present work is guided by the work “Paideia. The formation of the Greek man” by Werner Wilhelm Jaeger who developed reflections on the mythological, sophistical, philosophical texts and political, cultural and spiritual events of Classical Greece. Guided by the historical-evolutionary method, he proposed that History is a continuous awakening and that education should be analyzed in a particular and collective way. It focused on the demonstration of the image of the elevated Man, physical and psychic, which was already ingrained in the consciousness of the Greeks. It analyzed Socratic pedagogy, the result of a historical process that preceded it and an educational landmark that left legacies, to build the center of Greek education. Appreciating poets, statesmen and philosophers of the period, he sought the structuring of areté and the study of Greek paideia as a totalizing education. Finally, this dissertation will go through the steps of Jaeger, philosopher and philologist, to know the ideal of Greek Man, the formulation of the true paideia and its space in the classical period.